Image-based screening for stress granule regulators: macro for the automated detection and quantification of stress granules - Eiermann, Nina; Stoecklin, Georg (Universität, 2021)
The supplied macro provides the opportunity to analyse large-scale image datasets, derived from image-based screening approaches. It can be used as...
Kind of data: Program source code
Gesehen am 07.01.2021
Keywords: Forschungsdaten; Datenbank